Swimming Learning Method Early Childhood - M. Imran Hasanuddin Imran; Muhammad Akbar Syafruddin; Retno Farhana Nurulita Retno; Muhammad Qasash Hasyim (Universitas Majalengka, 2023)
The purpose of this research is to learn new things and make discoveries. The second is to show or validate the accuracy of previously held beliefs, and the third is to ascertain how the model of early childhood swimming develops. This research was conducted in a library. The research data is secondary. The documentation method of data collection is used in this research. Article content analysis is a technique used for analysis. When research articles meet the criteria, they are submitted, and a journal summary is prepared, which includes the name of the researcher, year of publication of the journal, study design, objectives, sample, tools (such as measurement instruments), and research summary. findings. There are ten publications that discuss swimming learning models in early childhood; all of these publications are national journals. To find it, use the keyword